Pupil. Book 2 - Law, Karina ([S.l.] : HarperCollins UK, 2008)
Written by teachers for teachers to perfectly support the renewed framework, Collins Primary Literacy is a whole school language program that builds key reading, writing, speaking and listening skills through structured creative work. It provides practical teaching ideas and clear assessment for every unit, so that you can focus on teaching. With fiction, non-fiction and poetry by best children's authors for your class to read and explore, Collins Primary Literacy provides engaging activities matched to the Renewed Framework that will save you time and give you lots of ideas. Each unit is built around three distinct phases - Engage, Explore and Create - during which children move through a learning pathway that develops key literacy skills. Active learning is at the heart of Collins Primary Literacy, with an emphasis on speaking, listening and drama work. Children are encouraged to work reflectively, with built-in opportunities for paired work and critical thinking. Opportunities for assessment are threaded throughout the teaching sequence, with further support given in the form of progress sheets for assessing writing.